2009
DOI: 10.1002/smll.200800919
|View full text |Cite
|
Sign up to set email alerts
|

CMOS‐Compatible Nanowire Sensor Arrays for Detection of Cellular Bioelectricity

Abstract: Perfectly aligned arrays of long silicon nanowires fabricated using a top–down complementary metal oxide semiconductor (CMOS) compatible approach and their ability for real‐time extracellular recording of cellular bioelectricity are presented. The technique enables noninvasive, high‐sensitivity, high‐throughput, long‐term electrophysiology measurements at the single‐cell level or from tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
101
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 22 publications
2
101
0
Order By: Relevance
“…So far, the coupling of NWs to cells has been demonstrated once with neuronal cells 6 and in a very recent publication with cardiomyocytes and aortic smooth muscle cells. 7 However, the signal shapes in these studies were different from previous recordings with planar transistors and so far are not well understood.…”
mentioning
confidence: 57%
“…So far, the coupling of NWs to cells has been demonstrated once with neuronal cells 6 and in a very recent publication with cardiomyocytes and aortic smooth muscle cells. 7 However, the signal shapes in these studies were different from previous recordings with planar transistors and so far are not well understood.…”
mentioning
confidence: 57%
“…More recently, several groups have demonstrated electrical interfaces with cells and tissue using NWFETs and carbon nanotubes (CNTs) (14)(15)(16)(17). Interestingly, studies have shown clearly that NW and CNT devices have substantially higher sensitivity than planar FETs for detection of binding and unbinding of proteins, nucleic acids, and even single virus particles (18)(19)(20)(21)(22)(23) and thus can also offer advantages for cellular recording.…”
mentioning
confidence: 99%
“…Interestingly, studies have shown clearly that NW and CNT devices have substantially higher sensitivity than planar FETs for detection of binding and unbinding of proteins, nucleic acids, and even single virus particles (18)(19)(20)(21)(22)(23) and thus can also offer advantages for cellular recording. Indeed, NWFET studies have demonstrated high-S/N recording from cultured neurons, muscle cells and embryonic chicken hearts (14)(15)(16). A unique feature of these studies compared with conventional planar devices measurements is that the nanodevices protrude from the plane of substrate, and hence can increase NW/cell interfacial coupling.…”
mentioning
confidence: 99%
“…A separate group also demonstrated that lithographically patterned top-down NW FETs can be used to record signals from rat cardiomyocytes and monolayers of rat aortic smooth muscle cells with high S/N and mV amplitudes [42]. In our own laboratory, we investigated cultured cardiomyocyte monolayers in a new manner and probed the relationship between interfaces and signal magnitude [43].…”
Section: Transparent and Flexible Substratesmentioning
confidence: 99%